Implementasi Pembelajaran Pendidikan Agama Islam dalam Membentuk Kesadaran Beragama di SDIT Mardhatillah Kabupaten Sukoharjo - Falakh, Afif Nurohman; Suja’i, Ahmad; Huda, Miftahul (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
The decline in the level of religious awareness in children is caused by various factors, one of which is the increasingly rapid progress of the times and technology, which demands realistic and structured actions in an effort to increase the quality of religious awareness in children. This study aims to describe and analyze the implementation of Islamic Religious Education (PAI) learning methods in forming religious awareness of students at SDIT Mardhatillah using implementation theory. The policy implementation theory used in this study is Grindle's theory, which emphasizes five main aspects, namely policy formulation, content of policy and context of implementation, implementation process by actors, and level of implementation success.This study employed a descriptive qualitative methodology, with data collection techniques conducted through observation, in-depth interviews, and documentation with the principal, Islamic Religious Education teachers, and students as research subjects. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of the study show that the implementation of the PAI learning method at SDIT Mardhatillah in forming religious awareness was successful in forming students' religious awareness which is reflected in their attitudes, behavior, and daily religious practices.